2013
DOI: 10.1080/13698575.2013.764974
|View full text |Cite
|
Sign up to set email alerts
|

Gypsies/Travellers and health: risk categorisation versus being ‘at risk’

Abstract: Risk categorisation provides a routine and necessary contribution to the way people make sense of and impute predictability in a complex human world of which their knowledge is limited. It is a precursor to the development of risk management strategies. Risk categorisation schemes can vary depending on the underlying perspective and knowledge used in their construction. There are estimated to be between 120,000 and 300,000 Gypsies and Travellers in the UK. They have been categorised on the one hand as a group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In terms of lay understanding, Jesper et al (2008) found that some Gypsies and Travellers described the nature of cancer not in relation to the physiological body but as a distinctly gendered disease, particularly in terms of who may be prone to it. Other studies identify a belief that the disease is contagious (Twiselton and Huntington, 2009), -while others report a belief that discussing cancer can make one more susceptible to it (Ruston and Smith, 2013). Some Gypsies and Travellers also believe that a bad diagnosis from a health professional can actually harm the patient's overall resilience (Welsh Government, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of lay understanding, Jesper et al (2008) found that some Gypsies and Travellers described the nature of cancer not in relation to the physiological body but as a distinctly gendered disease, particularly in terms of who may be prone to it. Other studies identify a belief that the disease is contagious (Twiselton and Huntington, 2009), -while others report a belief that discussing cancer can make one more susceptible to it (Ruston and Smith, 2013). Some Gypsies and Travellers also believe that a bad diagnosis from a health professional can actually harm the patient's overall resilience (Welsh Government, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the average length of life in this group was 10 to 12 ages less than the general population [8]. A study by Özdemir et al determined that 78.8% of the elder population living in Sivas had chronic diseases [21].…”
Section: Discussionmentioning
confidence: 89%
“…The researchers decided that this number was not sufficient for the study. Considering that the average life expectancy is 10 to 12 ages shorter in the Romani people than in the general population [8], the Romanis aged 60 and older were also included in the study population.…”
Section: The Population and Sample Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The extent to which people feel in control over where and how they live is also significant in influencing health and wellbeing outcomes. Lack of control and ability to manage housing environments often has a crucial health-damaging effect on a marginalised social status and exacerbates existing health inequalities (Van Hout and Staniewicz, 2012;Ruston and Smith, 2013). The criminalisation of unauthorised camping and a decline in public site vacancies following the 1994 Criminal Justice and Public Order Act has precipitated a drift into 'conventional' and 'settled' housing over recent decades as options to live a nomadic life, or to reside on campsites, have been significantly curtailed post-1994.…”
Section: Introductionmentioning
confidence: 99%